Implanting Character Education in the Young Generation Through Wedhatama Fibers - Setyo Pambudi; Machasin Machasin; Sedya Santosa (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
The impact of the globalization era is very influential on the character of the younger generation today, especially students. There are many impacts that we can feel with the current era of globalization which has a major influence on the character of students. To overcome the degradation impact of the current globalization era, we must try to re-instill character education in students. This is so that students can slowly reduce and even get rid of actions that are not commendable. There are many ways we can re-instill character education in students. One of them is through literature. Literary works are very diverse, one of which is the literary work “Serat Wedhatama”. The research aims to instill character education in students through the texts in “Serat Wedhatama”. The research is included in qualitative research, the primary data in this study are the texts of “Serat Wedhatama”, while the secondary data in this study are books, journals, and others that can support the success of this research. The results of this study include, 1) the text “Serat Wedhatama I” contains religious character education devoted to God Almighty; 2) the text “Serat Wedhatama II” contains religious character education inculcating a sense of tolerance; 3) the text “Serat Wedhatama III” contains religious character education of perseverance in worshiping God Almighty; and 4) in the text “Serat Wedhatama IV” contains religious character education living guided by Islamic principles.